Faktor Prognostik yang Mempengaruhi Terjadinya Komplikasi Dini Enterokolitis dan Konstipasi pada Penderita Hirschsprung yang Dioperasi dengan Tehnik ERPT di RSUP Dr Sardjito - , AHKOB KRISNANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Hirschsprung disease is a congenital abnormality in the large bowel which is characterized by the absence of parasymphathetic ganglionic cells in the submucosal plexus of Meissner and myenteric plexus of Auerbach. The diagnosis of megacolon is confirmed by clinical examination, laboratorical examination, histopatology and radiology. Hirschsprung disease is the most common abnormality which causes obstruction and enterocolitis in children with incidence rate of 1 : 5,000 per live birth. Soave procedure which is an extramucosal endorectal technique is one of the surgical procedure applied for the definitive treatment of Hirschsprung disease. Objective. This study was aimed to achieve a clear description about enterocolitis complications and constipation after surgery using Soave procedure, and at the same time, to detemine the contributing factors . Subject of Study. We used secondary data in the form of the medical records of Hirschsprung disease patients who underwent surgery using Soave procedure in dr.Sardjito Hospital from January 2005 to December 2012. Collected data included sex, history of meconium passage, age at presentation, nutritional status, pre-operative haemoglobin level, pre-operative albumin level, duration of surgery, length of stay, preoperative and post-operative incidence of enterocolitis and constipation. Methods. This study was an observational analysis, with a non-experimental retrospective cohort study design. We used chi-square test and logistic regression test for statistical analysis, with significant value p < 0.05. Result. There were 88 cases in this study population, consisted of 62 male patients (70%) and 26 female patients (30%). Pre-operative incidence of enterocolitis was 23 cases (26.1%), and the other 65 (73.9%) did not show any signs of enterocolitis. After ungoing surgery with Soave procedure, post-operative incidence of enterocolitis decreased into 22 patients (25%), whereas the other 66 patients (75%) had no signs of enterocolitis. The statistical analysis using chi-square test resulted in p value < 0.01. Conclusion The incidence of enterocolitis after Soave procedure decreased, and there was a significant correlation between the proportion of pre-operative and post-operative incidence of enterocolitis, proven by statistical analysis with p value < 0.01. In the other hand, factors such as sex, first meconium passage, age at presentation, nutritional status, pre-operative haemoglobin level, pre-operative albumin level, duration of surgery, length of stay, pre-operative incidence of enterocolitis and constipation did not have any statictical significance with the post-operative incidence of enterokolitis and constipation.